Oxford Scholarship Online 2017
DOI: 10.1093/oso/9780198758631.003.0003
|View full text |Cite
|
Sign up to set email alerts
|

Which Face Comes First? The Ascendancy of the Party in Public Office

Abstract: Recently, students of European parties have come to agree that organizational power has been concentrating in the party in public office (PPO), whose particular interests and objectives shape those of the party at large. This process of growing autonomy of the PPO—hypothesized by Katz and Mair—goes hand in hand with that of party penetration of the state and with a corresponding decline of party presence within civil society. This chapter aims to verify, empirically, if the PPO is indeed moving in the directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…In both parties, MPs have strengthened their hold of leadership positions and the PPO's financial and staff resources have increased considerably, while the PCO's financial resources have stagnated and staff resources have even decreased. Recent comparative studies have found similar developments (Bardi et al, 2017). This study's findings confirm the suspicions raised by earlier studies: the PCO/PPO resource distribution can change towards the cartel model, while the distribution of (formal) decision-making power remains stable.…”
Section: Resultssupporting
confidence: 88%
“…In both parties, MPs have strengthened their hold of leadership positions and the PPO's financial and staff resources have increased considerably, while the PCO's financial resources have stagnated and staff resources have even decreased. Recent comparative studies have found similar developments (Bardi et al, 2017). This study's findings confirm the suspicions raised by earlier studies: the PCO/PPO resource distribution can change towards the cartel model, while the distribution of (formal) decision-making power remains stable.…”
Section: Resultssupporting
confidence: 88%
“…But it is not a question of numbers, whose decline is unequivocal (Bardi et al, 2017), safe exceptions such as the amazing increase in the Labour party under Jeremy Corbyn's leadership. The real trouble concerns the different meaning that, in present times, enrolling in a party has with respect to the era of the mass party.…”
Section: Introductionmentioning
confidence: 99%
“…Although records have been kept by the NEC since 1992, Specifically, for the analysis of internal power shifts, this article focuses on two empirical indicators commonly used in the existing literature: the number of salaried party staff members at the PCO and the number of party executives and candidates selected through competitive elections (e.g. Bardi et al, 2017;Katz & Mair, 2009;Van Biezen, 2003). If there has been a power shift within a party, we expect the number of salaried staff members at the PCO to be reduced, and competitive elections to be used for the selection of party executives and candidates more frequently than the appointment by party leaders.…”
Section: Data and Operationalisationmentioning
confidence: 99%